Potensi Bakteri Saluran Pencernaan Ikan Sidat Sebagai Antibiotik - Diah Puspita Sari; Wahyuni Sultan; Abdullah Rasyad; Diah Kusumawaty (PT ADRIANI MANDIRI PUBLISHER, 2026)
Anguilla bicolor bicolor is a species of eel found in Indonesian waters. This species of eel has a high economic value and the export commodity of eel has increased, especially in Japan. Bacteria in the digestive tract of eels have the potential as antibiotics which is one way of treating and preventing diseases in the fisheries sector. This study aim to identify bacteria in the digestive tract of eel that have the potential as antibiotics. The search for data on eel digestive tract bacteria that have the potential as antibiotics was carried out by reviewing literature and secondary data then analyzed descriptively and processed using Microsoft Excel and Microsoft Word. The result showed from metagenomic data, obtained 3 genera of bacteria that have the potential as antibiotics, Bacillus, Enterococcus, and Streptomyces. In the eel elver wild phase, the bacteria that had the highest abundance was the genus Bacillus. In the eel fingerling wild phase, the highest abundance of bacteria was from the genus Enterococcus.